Pulmonary and Intestinal Congenital Anomalies Masquerading as Cystic Suprarenal Masses - Ballouhey, Quentin; Abbo, Olivier; Baunin, Christiane; Pasquet, Marlène; Sartor, Agnès; Vayssiere, Christophe; Guitard, Jacques; Galinier, Philippe (European Journal of Pediatric Surgery, 2012)
Objectives The prenatal finding of a cystic suprarenal mass (CSM) presents a wide differential diagnosis. The aim of this study was to present the natural course and outcome of antenatally diagnosed CSMs.Methods We reviewed the medical records of patients with prenatally detected CSMs that were assessed between January 1998 and December 2011. Retrospective data collection included the age at the time of diagnosis, the size of the mass, and the sonographic evolution of the mass. Surgical treatment was indicated in cases of malignant tumors and symptoms or when size increased.Results The observation period ranged from 1 month to 10 years. The data of 21 patients were analyzed. The median length of follow-up was 32 months (ranging from 2 to 131 months). A total of 13 masses were detected on the left side and 8 on the right side. In 13 patients, the lesions disappeared after a median of 7 months (ranging from 0 to 37 months). Surgery was performed in two neonates: one for a teratoma at 10 days postpartum, and one for a neuroblastoma at 17 days postpartum. Six patients had an extralobar pulmonary sequestration (ELPS), and in four patients, surgical resection was performed at an average of 9.2 months (ranging from 1 to 20 months) postpartum, because of an infection or increase in ELPS size. Histological examination confirmed the pulmonary sequestration. An association with congenital cystic adenomatoid malformation (CCAM) was found in one patient, and ectopic pancreatic tissue was discovered in another patient. Two patients conservatively managed remain under observation.Conclusions During the neonatal period, the accurate assessment of CSMs is necessary to exclude the presence of malignant tumors. Most patients can be conservatively managed, with close follow-up, including radiological assessment. If the mass persists after 1 year of age, ELPS should be considered as a probable diagnosis, and minimally invasive laparoscopic surgery can be performed, as it provides both definitive diagnosis and treatment.
Keywords: prenatal ultrasonography; extralobar bronchopulmonary sequestration; minimally invasive surgery